2013
DOI: 10.1002/pbc.24746
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in children with brain tumors in the first year after diagnosis compared to healthy matched controls

Abstract: Early cognitive impairment is present in BT children, sometimes prior to radiotherapy/chemotherapy treatment, and is associated with hydrocephalus, high tumor grade and infratentorial site. Future studies should investigate the role of early rehabilitation in improving cognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 46 publications
4
33
0
1
Order By: Relevance
“…Longitudinal studies are more rare, but have also pointed to a decline over time in global IQ and most neuropsychological indices among patients with brain tumors. Linear modeling suggests declines of 1.5–2 points per year in first 5 years post radiotherapy treatment for brain tumors, without consistent evidence of nadir or leveling off …”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal studies are more rare, but have also pointed to a decline over time in global IQ and most neuropsychological indices among patients with brain tumors. Linear modeling suggests declines of 1.5–2 points per year in first 5 years post radiotherapy treatment for brain tumors, without consistent evidence of nadir or leveling off …”
Section: Resultsmentioning
confidence: 99%
“…However, three other patients in this cohort, who only had CSF diversion surgery for their tectal plate gliomas, had significant deficits on neuropsychological testing. This suggests that the presence of a brain tumor, prior neurosurgery or prior hydrocephalus could impact neurocognitive outcome and school functioning [24].…”
Section: Discussionmentioning
confidence: 99%
“…Another study examining the effect of chemotherapy‐only treatment on cognitive outcomes found this treatment to be strongly related to attention deficits in survivors of childhood acute lymphoblastic leukemia . Studies have also suggested a relation between hydrocephalus and attentional deficits . In fact, both chemotherapy and hydrocephalus have been linked to reduced white matter volume, which is reported to be strongly related to attentional deficits .…”
Section: Discussionmentioning
confidence: 99%